ANALISIS MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMA NEGERI 1 X KOTO TANAH DATAR - Hafidah Dinatul Latifah (Departemen Matematika, 2021)
The purpose of this research to describe learning motivation mathematics and students' mathematics learning outcomes, and describe whether there is an impact of motivation to learn mathematics on math learning result XI grade students of SMAN 1 X Koto Tanah Datar. This type of riset is a quantative descriptive riset with quantitative. The population in the riset were XI grade students of SMAN 1 X Koto Tanah Datar. Samples riset were taken by“purposive sampling technique”, so we get class XI IPS 2 and XI IPS 3 SMAN 1 X Koto Tanah Datar were selected as the research sample. Results of the research showed that (1) The motivation for learning mathematics for students class XI SMAN 1 X Koto Tanah Datar in general, it has a medium category with the average value obtained 71,17. (2) motivation to learn mathematics in each category,it has a moderate category and average percentage are 74,37%. (3) Results In general, studying mathematics for class XI SMAN 1 X Koto Tanah Datar students are in the medium category with an average of 74. (4) the learning motivation of mathematics has a significant influence significant to outcomes of math learning, influence of motivation on mathematics learning outcomes is 6,4%, the remaining 93,6% are not influenced by the motivation to learn mathematics but are influenced by other factors. Keywords – Analysis, Learning Motivation, Learning Outcomes, Mathematics.